EDITORIAL: The Scope of Teaching and Learning in Environmental Education - Heila Lotz Sisitka (Environmental Association of Southern Africa, 2010)
Environmental Education involves a variety of teaching and learning processes which are diversely situated in a range of social and educational contexts. The diversity of scope is an interesting 'contour' of a field like environmental education. Contemporary environmental sciences and complexity studies draw our attention to an ever-changing world and to increasingly complex social-ecological issues, patterns and risks that require our attention. These too influence the scope of environmental education teaching and learning processes. This edition of the Southern African Journal of Environmental Education provides a window through which we may see some of the scope of environmental education activities, research questions, learning and teaching settings, and educational activity. It provides insight into the range of research methodologies that are being deployed to investigate the educational processes that are needed for re-orientation towards sustainability, equity, adaptability and transformation at the people-environment interface.